Hölderlin pensando no ritmo, Hegel pensando o ritmo da tragédia: duas abordagens complementares da tragédia (Revista Eletrônica Estudos Hegelianos, 2021)
: Hölderlin is often regarded as a poet whose ideas differ significantly from Hegel’s systematic thinking. This article clarifies that the differences between these two philosophers should not overshadow important convergences in their readings and conceptions of tragedy and the tragic. In particular, we will deal with the points of contact between the Hölderlinian notions that guide the composition and understanding of tragic poetry (rhythm, caesura and counter-rhythmic movement), and the Hegelian concepts that systematize the movement of reflection within the tragic poem, and tragedy as an important phase in the Phenomenology of Spirit (movement of the concept, gliding of predicates within a proposition, the speculative counter-stroke which contains this slippage and brings forth the substantial logic of this movement).